“O Velho Marx”: humor and irony to the critique - Silva, Juliana de Paula Sales (2009)
This article intends to analyses the tale “O Velho Marx” (“The Old Marx”) by Moacyr Scliar in its humor, irony and critic features. The tale is showed as a fiction of the history in which is revealed, in reality, a critic about some social values. The power is seen here as an element that changes the human behavior promoting the illusion of the superiority among men.